Differentiating human pluripotent stem cells into vascular smooth muscle cells in three dimensional thermoreversible hydrogels. (28th November 2018) - Lin, Haishuang; Du, Qian; Li, Qiang; Wang, Ou; Wang, Zhanqi; Liu, Kan; Akert, Leonard; Zhang, Chi; Chung, Soonkyu; Duan, Bin; Lei, Yuguo
Abstract : 3D thermoreversible PNIPAAm-PEG hydrogels are used for scalable production of human pluripotent stem cell-derived vascular smooth muscle cells. Abstract : Vascular smooth muscle cells (VSMCs) are of great value and are needed in large quantities for tissue engineering, drug screening, disease modeling and cell-based therapies. However, getting high quantity VSMCs remains a challenge. Here, we report a method for the scalable manufacturing of VSMCs from human pluripotent stem cells (hPSCs). hPSCs are expanded and differentiated into VSMCs in a three dimensional (3D) thermoreversible hydrogel. The hydrogel not only acts as a 3D scaffold for cells to grow, but also protects cells from hydrodynamic stresses in the culture vessel and prevents cells from excessive aggregation. Together, the hydrogel creates a cell-friendly microenvironment, leading to high culture efficiency. We show that VSMCs can be generated in 10 days with high viability (>90%), high purity (>80%) and high yield (∼2.0 × 10 7 cells per mL hydrogel) in the hydrogel scaffold. The generated VSMCs have normal functions. Genome-wide gene expression analysis shows VSMCs made in the hydrogel ( i.e. 3D-VSMCs) have higher expression of genes related to vasculature development and glycolysis compared to VSMCs made in the conventional 2D cultures ( i.e. 2D-VSMCs), while 2D-VSMCs have higher expression of genes related to cell proliferation. This simple, defined and efficient method is scalable for manufacturing hPSC-VSMCs for various biomedical applications.